Complexity drivers in product development: A comparison between literature and empirical research - Wolfgang Vogel; Rainer Lasch (Logistics Research, 2018)
Companies in high-technology marketplaces are confronted with social, market-specific, technological and economical changes such as technology innovation, changing customer requirements, globalization of markets and competitions as well as market uncertainty. Manufacturing companies cannot escape these trends. For company's success, it is fundamental to bring new and high quality products quickly and with customer's individual settings to market. Product development is one of the most complex tasks and uncertain processes in the company. Complexity in product development comes from a variety of internal and external sources, so called complexity drivers. In literature, 108 complexity drivers in product development are described by several authors. To compare literature's information about complexity drivers in product development and their effects with the practice, an empirical study is needed. Currently, an empirical research regarding complexity drivers in product development in manufacturing companies and their effects does not exist. Covering this research gap is this paper's purpose. For this empirical study, a six stage systematic approach from Flynn et al. was applied, starting with the determination of the theoretical foundation and the research design as well as the selection of the data collection method. The data was collected in different fields of the German manufacturing industry through standardized questionnaires, which were sent by e-mail to 3,086 companies between 2015 and 2016. In total, 295 questionnaires were answered completely. The data was analyzed by using statistical methods. The empirical results regarding complexity drivers were compared with literature to identify communalities and differences. In literature, 108 complexity drivers and 18 effects are described. In contrast, 30 complexity drivers and 4 effects were mentioned by experts. Based on a factor analysis, the complexity drivers were aggregated to 7 factors, which reflect the complexity drivers.
Keywords: 650; Complexity; Complexity management; Complexity drivers; Product development; Empirical research